BURNOUT AKADEMIK DAN TANTANGAN MENJAGA HAFALAN AL-QUR’AN - Intan Aulia; Mabruka Az-zahra; Nurmadaniah Asma; Rajwa Luthfiyyah; Edi Hermanto (PT. Hasba Edukasi Mandiri, 2026)
This study aims to explore the lived experiences of academic burnout and the challenges of Qur'an memorization (tahfizh) among students of the Qur'anic Studies and Exegesis program, employing a qualitative phenomenological approach with data collected through in-depth interviews with purposively selected informants based on their active participation in the tahfizh program and observable indications of burnout, which were then analyzed using thematic analysis to identify patterns and themes reflecting the informants' subjective experiences. The findings reveal that students experienced various forms of academic burnout driven by heavy memorization loads, performance-related pressure, and insufficient recovery time, while the most frequently reported tahfizh challenges included difficulties in maintaining memorization consistency, concentration disruptions due to fatigue, declining intrinsic motivation, and inadequate social support, all of which directly and adversely affected the quality and quantity of students' Qur'anic memorization. This research is expected to provide deeper understanding for Islamic education stakeholders in designing tahfizh support systems that are attentive to students' mental well-being, as well as to serve as a foundation for developing more humane and sustainable academic policies.